2003
DOI: 10.1002/ccd.10662
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral valve repair: A feasibility study in an ovine model of acute ischemic mitral regurgitation

Abstract: Annuloplasty is the cornerstone of surgical mitral valve repair. A percutaneous transvenous catheter-based approach for mitral valve repair was tested by placing a novel annuloplasty device in the coronary sinus of sheep with acute ischemic mitral regurgitation. Mitral regurgitation was reduced from 3-4+ to 0-1+ in all animals (P < 0.03). The annuloplasty functioned by reducing septal-lateral mitral annular diameter (30 +/- 2.1 mm preinsertion vs. 24 +/- 1.7 mm postinsertion; P < 0.03). These preliminary exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 36 publications
0
67
0
Order By: Relevance
“…Percutaneous placement of mitral annuloplasty devices in the CS has been reported to reduce MR in models of global LV dysfunction 15 and acute ischemia. 16 Results from experimental models are encouraging. However, mechanisms that underlie these experimental forms of MR may differ from those present in chronic IMR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Percutaneous placement of mitral annuloplasty devices in the CS has been reported to reduce MR in models of global LV dysfunction 15 and acute ischemia. 16 Results from experimental models are encouraging. However, mechanisms that underlie these experimental forms of MR may differ from those present in chronic IMR.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 These studies in animal models of acute IMR and rapid pacing-induced heart failure demonstrated the feasibility of CS-based annuloplasty. However, it is essential to explore this approach in relevant models of chronic IMR similar to the human clinical situation.…”
Section: See P 2154mentioning
confidence: 97%
“…Annuloplasty is a common surgical strategy for ischemic/functional MR, however MR often persists after annuloplasty [12][13][14][15]. Recently, new surgical strategies have been expected to reduce chronic persistent ischemic MR after annuloplasty [16][17][18][19]. Understanding the precise mechanism of functional MR is a prerequisite in the complicated surgery, and 3D measurements provide important geometric information of the mitral valve apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to aortic valve devices, the ovine model is preferred for in vivo assessment of percutaneous mitral valve devices. To date, 2 types of diseased animal models were used in published data [76][77][78][79] . One type is the rapid-pacing heart failure model and the other type is the ischemic mitral regurgitation (MR) model.…”
Section: Mitral Valve Repairmentioning
confidence: 99%
“…The preclinical results have confirmed the feasibility of this approach for creation of an edge-to-edge repair 84 . 2) Annuloplasy: A variety of percutaneous technologies have been developed to alter mitral annular geometry such as coronary sinus-based annuloplasty, direct intracavitary annuloplasty, and other novel cinching devices [76][77][78][79]85 . Shortening or reshaping the annulus by insertion of a device into the coronary sinus has the potential to mimic surgical annuloplasty.…”
Section: Mitral Valve Repairmentioning
confidence: 99%